The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/2058738418797768
|View full text |Cite
|
Sign up to set email alerts
|

Marina crystal minerals (MCM) activate human dendritic cells to induce CD4+ and CD8+ T cell responses in vitro

Abstract: Marina crystal minerals (MCM) are a mixture that contains crystallized minerals along with trace elements extracted from seawater. It is a nutritional supplement that is capable of enhancing natural killer (NK) cell activity and increasing T and B cell proliferation in humans post ingestion. However, its effect on dendritic cells (DCs), the cells that bridge innate and adaptive immunity, is not yet known. In this study, we examine the stimulatory effects of MCM on DCs’ maturation and function in vitro. Human m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…pylori infection in mice, and further research on gastric carcinoma in situ will be conducted in future studies. Studies have shown that dendritic cells can stimulate CD4 + T to secrete a large amount of interferon (IFN‐γ) and stimulate CD8 + T cells to express higher levels of CD107a 47 . Moreover, mature DCs may enhance the infiltration of CD8 + T and CD4 + T cells into cancer cells 48‐50 …”
Section: Discussionmentioning
confidence: 99%
“…pylori infection in mice, and further research on gastric carcinoma in situ will be conducted in future studies. Studies have shown that dendritic cells can stimulate CD4 + T to secrete a large amount of interferon (IFN‐γ) and stimulate CD8 + T cells to express higher levels of CD107a 47 . Moreover, mature DCs may enhance the infiltration of CD8 + T and CD4 + T cells into cancer cells 48‐50 …”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that Biobran/MGN-3 (an arabinoxylan rice bran), PFT (a novel kefir product), and Marina Crystal Minerals (MCM; a mixture of crystallized minerals and trace elements extracted from seawater) all promote the production of inflammatory and anti-inflammatory cytokines. 27,31,32 Biobran and PFT also stimulate DC-primed CD4+ T cell proliferation and their production of IL-10, and MCM causes the upregulation of co-stimulatory molecules CD86, CD80, and HLA-DR. In addition, DPV576 (a dispersed aqueous mixture composed of nanodiamond and nanoplatinum) activates human DCs and upregulates the levels of DC-secreted cytokine IL-10, 33 and we have recently observed that exposure of human CD4+ T lymphocytes to DPV576 inhibits the activity of the transient receptor potential vanilloid channel TRPV1 in CD4+ T lymphocytes, suggesting that it has the potential for use in pain management.…”
Section: Discussionmentioning
confidence: 99%